La ordenanza que regula la fauna urbana en el GADM de Tulcán vulnera su régimen sancionatorio - Portilla Oliva, Domenica Carolinae (2024)
This article addresses the critical situation of animal abuse in Tulcán, where the current ordinance does not guarantee effective protection of urban fauna. It was identified that the current sanctioning regime is insufficient to deter cruel behaviour towards animals, which represents a violation of their legal security. The objective was to legally analyze the violation of the legal security of article 10 of the prohibited acts against urban fauna and its sanctioning regime of the Ordinance that regulates the possession, control and management of Urban Fauna in the Tulcán Canton, with the purpose of reforming the Ordinance with the accession of more cruel acts and their sanctions for the effective implementation and protection of animal rights. The modality used was quantitative with a cross-sectional methodological design and a descriptive scope. Furthermore, the hypothetical-deductive and analyticalsynthetic methods were applied. At the empirical level, documentary analysis was used as the main technique. The population considered was 100 people proportionally located in the neighborhoods of Estadio Olímpico, Ciudadela 2 de junio, and neighbordood 13 de junio. Through techniques such as surveys and interviews, it was determined that most respondents consider the current regulations to be ineffective. Furthermore, it was found that the lack of updating of the ordinance hinders the protection of animals. Environmental law experts interviewed stressed the urgency of incorporating more severe economic sanctions. The study concludes that it is necessary to reform the ordinance, integrating prohibited acts from the Comprehensive Organic Criminal Code (COCC) to strengthen the protection of animals and guarantee their wellbeing in Tulcán.